Long-Term Promotive and Protective Effects of Early Childcare Quality on the Social–Emotional Development in Children - Wustmann Seiler, Corina; Sticca, Fabio; Gasser-Haas, Olivia; Simoni, Heidi (Frontiers in Psychology, 2022)
The present study aimed to examine the longitudinal promotive and protective role of process quality in regular early childhood education and care (ECEC) centers in the context of early cumulative family risks on children’s social–emotional development from early to middle childhood. The sample consisted of 293 (T1; Mage = 2.81), 239 (T2; Mage = 3.76), and 189 (T3; Mage = 9.69) children from 25 childcare centers in Switzerland. Fourteen familial risk factors were subsumed to a family risk score at T1. Parents and teachers reported on children’s conduct problems (CP), emotional problems (EP), and prosocial behavior (PB) at T2 and T3. Childcare process quality was assessed at T2 using external observations of teaching and interaction, provisions for learning, and key professional tasks. Results showed that early family risks were positively associated with CP and EP and negatively associated with PB in the long term. High-quality teaching and interaction as well as caregivers’ professional behavior in terms of systematic observation, documentation, and planning of children’s individual learning processes and needs protected children from the undesirable long-term effects of early family risks on conduct problems, emotional problems, and prosocial behavior from early to middle childhood. The results indicate that a high process quality in ECEC might serve as an essential contextual protective factor in the development of resilience in children at risk.